Efeito da terapia fotodinâmica antimicrobiana mediada por curcumina sobre Streptococcus Mutans - Paschoal, Marco Aurelio Benini [UNESP] (2013)
This work investigated the antimicrobial photodynamic potential (PACT) mediated by a natural photosensitizer (PS), curcumin (C), exposure to an source of blue LED (L) applied over a Streptoccocus mutans (SM) mature biofilm formed on hidroxiapatite discs and compared this potential with biofilms submitted to single immersion of chlorhexidine at 0.12% (CHX). Additionally, it was verified the efficacy of a broad visible spectrum light source (white light) of high potency intensity in the presence of C and toluidine blue (T) at low concentrations and exposure to an extra short illumination time. Materials: SM biofilms were submitted to a treatment with C solutions and exposure to a 48 J/cm2 e 72 J/cm2 of L and immersion in CHX. Furthermore, a white light source (42 J/cm2; 3410 mW/cm2) was used in the presence of low concentrations of C and T for an extra short period over SM suspensions. The efficacy of the treatments were performed by colony forming units counting (CFU/mg of dry biofilm and CFU/ml of suspension) and the morphological analysis of biofilms were performed using confocal laser scanning microscopy images and environmental scanning electron microscopy. Results: PACT (C at 2.5 mM and L at 48 J/cm2) presented a bacterial substantial reduction when compared with CHX treatment. The white light showed lethal photossensibilization in the utilized parameters. Conclusion: The use of curcumin, a natural compound and the white light, able to activate FS at shorts periods, are advance on this antimicrobial alternative field.